DAMPAK PENDAYAGUNAAN ZAKAT PRODUKTIF UNTUK KETAHANAN USAHA MIKRO, KECIL, DAN MENENGAH DI KOTA TANGERANG - Deni Nuriadin (Adisam Publisher, 2024)
The utilization of productive zakat is an important element in the development of MSME actors. The purpose of this study is to confirm the extent of the impact caused by MSME actors. The subjects of this study were taken from recipients of productive zakat. The results of the study indicate that several good MSME actors are able to encourage growth in product turnover. Continuous mentoring of MSME actors has been empirically proven to be able to strengthen MSME actors towards a higher level. The impact of productive zakat is very large for the development of MSME actors who contribute directly to the economy of the city of Tangerang. Strong MSME actors also have an impact on better zakat receipts in the future.